The Secret of Sandwich Generational Resilience: Finding Mental Well-Being Through Attachment to God - Christina Widhigdo, Jessica; Hery Saputra, Christine; Chrestella Valencia, Shannon (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
The sandwich generation faced high psychological pressure due to dual responsibilities in caring for elderly parents and children while also meeting economic demands. Psychological factors, such as attachment to God, could serve as an effective coping mechanism in enhancing their resilience and mental well-being. This study aimed to examine the role of attachment to God in mediating the relationship between resilience and mental well-being in the sandwich generation. A quantitative research approach with a correlational design was employed, where data were collected through questionnaires distributed to individuals categorized as part of the sandwich generation (N = 250) and analyzed using mediation regression techniques. The findings indicated that attachment to God played a significant role in strengthening the effect of resilience on mental well-being. Individuals with a high level of attachment to God demonstrated greater resilience and higher mental well-being compared to those with lower attachment. The implications of this study highlighted the importance of spirituality in psychological intervention strategies for the sandwich generation, suggesting that spirituality-based programs, such as faith-based therapy or religious community support, could serve as effective approaches to enhancing their mental resilience. Generasi sandwich menghadapi tekanan psikologis tinggi akibat tanggung jawab ganda dalam merawat orang tua lanjut usia dan anak-anak sekaligus memenuhi tuntutan ekonomi. Faktor psikologis seperti kelekatan kepada Tuhan dapat menjadi mekanisme koping yang efektif dalam meningkatkan resiliensi dan kesejahteraan mental mereka. Penelitian ini bertujuan untuk menguji peran kelekatan kepada Tuhan dalam memediasi hubungan antara resiliensi dan kesejahteraan mental generasi sandwich. Metode penelitian yang digunakan adalah pendekatan kuantitatif dengan desain korelasional, di mana data dikumpulkan melalui kuesioner yang disebarkan kepada individu dalam kategori generasi sandwich (N = 250) dan dianalisis menggunakan teknik regresi mediasi. Hasil penelitian menunjukkan bahwa kelekatan kepada Tuhan berperan signifikan dalam memperkuat efek resiliensi terhadap kesejahteraan mental. Individu dengan tingkat kelekatan kepada Tuhan yang tinggi menunjukkan tingkat resiliensi yang lebih baik serta kesejahteraan mental yang lebih tinggi dibandingkan mereka yang memiliki kelekatan rendah. Implikasi penelitian ini menyoroti pentingnya aspek spiritual dalam strategi intervensi psikologis bagi generasi sandwich, di mana program berbasis spiritualitas seperti terapi berbasis keimanan atau dukungan komunitas keagamaan dapat menjadi pendekatan efektif dalam meningkatkan ketahanan mental mereka.